(untitled) (Research, Society and Development, 2020)
Concept mapping consist of diagrams that represent the relationships between concepts and words that describe them. The present study aimed to examination of student perceptions of using concept mapping in a pharmacy course. A group of undergraduate students from the sixth semester were the participants. Students received the concept mapping before and after the theoretical class, also could make their own map. In general manner, 97% of the students made use of concept mapping, 90% consider that their use may be useful for learning pharmacology. 50% of participants considered the help provided by concept mapping for their learning as satisfactory, 25% as very satisfactory and 25% as regular. Still, 63% of students intend to continue use of conceptual maps and 34% think about continuing to use concept mapping. Therefore, the study demonstrated that use of concept mapping as a teaching tool for pharmacology class, managed to arouse students interest in contents.